Entrepreneurial Intention In The Perspective Of Entrepreneurship Education And Individual Entrepreneurial Orientation - Kumorowati, Indah; Yogie Dana Insani; Herla Lukmanasari; Rahmawati; Andy Prasetyo Wati; Fulgentius Danardana Murwani (International journal of technology and education research, 2025)
This study aims to examine the relationship between Entrepreneurial Education (EE), Individual Entrepreneurial Orientation (IEO), and Entrepreneurial Intention (EI) through a systematic review method based on the PRISMA approach. Data were collected from the Scopus database with studies published in the last five years (2021-2025). The results of the analysis show that entrepreneurship education has a positive effect on increasing individual entrepreneurial orientation and entrepreneurial intention. In addition, individual entrepreneurial orientation proved to be an important mediator in strengthening the relationship between entrepreneurship education and entrepreneurial intention. Other findings revealed that the effectiveness of entrepreneurship education is influenced by practical experience factors, cross-disciplinary integration, as well as learning environment support. This study confirms the importance of a structured entrepreneurship education program in building competence, confidence, and entrepreneurial readiness among university students. The implication of this study provides a new direction for the development of individual competency-based entrepreneurship curriculum